Development of Interactive Learning Media Assisted by Filmora on Algebraic Forms Material - Widiyasari, Ririn (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The objective of this research is to develop interactive learning media assisted by Filmora for algebraic forms material. The research and development model used is model by ADDIE stages (Analysis, Design, Development, Implementation, Evaluation). This study was conducted at MTs Muhammadiyah 1 Ciputat with the research subjects consisting of seventh-grade students and a mathematics teacher. The results show that the learning media assisted by Filmora is valid for use based on expert validation results, with an average score of 90.71% from media experts, 93.06% from material experts, and 92.72% from language experts. The small-group trial indicated that the Filmora-assisted learning media is highly practical, with student responses averaging 85.81% and teacher responses averaging 86.11%. Meanwhile, in the large-group trial, the students' response score averaged 88.87%, categorized as very practical. The effectiveness level was 80% in both the small-group and large-group trials. Based on these findings, it can be concluded that the Filmora-assisted learning media is valid, practical, and effective for teaching algebraic forms in mathematics. The results of this research are expected to benefit teachers, students, future researchers, and other related parties.